An outbreak of Glasser’s disease from two farms in Malaysia - Khaing, Aung Tun; Ching, T. S.; Abba, Yusuf; Abdullah, Faez Firdaus Jesse; Osman, Abdinasir Yusuf; Adamu, Lawan; Mohammed, Konto; Tijjani, Abdulnasir (Global Researchers Journals, 2014)
Haemophilus parasuis is an endemic bacterial pathogen in pig farms worldwide. In this report, we investigated a suspected case of Glasser’s disease in 3-9 weeks old Landrace cross Duroc piglets from two pig farms. The farmers reported the case to the Veterinary Hospital of University Malaysia Kelantan, with the complaint of anorexia, depression and weakness. On physical examination, the piglets were found to be smaller in size and had rough hair coat. Clinical signs included swollen hock joint, labored abdominal breathing and tremors. Post-mortem evaluation of culled moribund piglets showed pneumonic lesions in the lung, polyarthritis of the hock joint, cerebral congestion, meningitis, renal cortical heamorrhage and polyserositis. Histo-pathological examination showed interstitial pneumonia with emphysema, encephalitis, encephalomalacia with gliosis and vacuolar degeneration of the hepatocytes. Bacteriological culture of swab samples from infected organs revealed the growth of satellitic small colonies on blood culture suggestive of H. parasuis. Ceftiofur injection (HIPRA, Malaysia, 3mg kg-1i.m), phenoxymethyl penicillin (Norvatis Animal Health, Australia at 200g T-1 of feed) and amoxicillin (Norvatis Animal Health at 15-30g 100L-1 of water) were effective in reducing morbidity and reversing clinical signs. Prompt diagnosis and treatment of Glasser’s disease in pig farms is paramount in order to curtail its menace and prevent serious economic losses.